Pembagian Aset Digital Dalam Hukum Waris Islam: Antara Norma Dan Realitas Di Indonesia - Muhammad Rusli (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2026)
The development of digital technology has introduced new forms of wealth in the form of digital assets, which possess economic value but are not yet fully accommodated within the Islamic inheritance law system in Indonesia. This condition creates a tension between normative legal provisions and evolving social realities. This study aims to analyze the status of digital assets as inheritance objects within the framework of Islamic inheritance law and to examine the challenges in their distribution within the context of Indonesian positive law. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that digital assets can be classified as property (al-māl) as they fulfill the elements of economic value, ownership, and utility, despite their intangible nature. However, in practice, the distribution of digital assets faces several challenges, including limited access, digital security systems, and the absence of explicit regulation in the Compilation of Islamic Law. This situation reflects a gap between legal norms and social realities (legal lag) within the inheritance system. Therefore, a more adaptive approach is required through the integration of maqāṣid al-sharī‘ah principles to ensure that Islamic inheritance law remains responsive, just, and contextual in addressing the development of digital assets.